Aluminum-Based Metal–Organic Frameworks Derived Al2O3‑Loading Mesoporous Carbon as a Host Matrix for Lithium-Metal Anodes - Zhang, Shao-Jian; You, Jin-Hai; Chen, Jian-De; Hu, Yi-Yang; Wang, Chuan-Wei; Liu, Qian; Li, Yu-Yang; Zhou, Yao; Li, Jun-Tao; Światowska, Jolanta; Huang, Ling; Sun, Shi-Gang (ACS applied materials & interfaces, 2019)
Li-metal anode attracts great focus owing to its ultra-high specific capacity and the lowest redox potential. However, the uncontrolled growth of Li dendrite leads to severe security issues and limited cycle life. Herein, Al2O3 loading mesoporous carbon (Al2O3@MOF-C) derived from Al-based metal–organic frameworks (Al-MOFs) was investigated as the stable host matrix for Li metal, in which, Al2O3 was served as nano seeds for the Li deposition and decrease the Li nucleation overpotential. Except that, the high specific surface area and wide pore distribution can also buffer the volume changes of Li and fasten electron transfer, hence a dendrite-free morphology was observed even after 50 cycles at 2 mA cm–2. High Li coulombic efficiency of 97.9% after 100 cycles at 1 mA cm–2, 1 mAh cm–2, and 97.6% after 50 cycles at 1 mA cm-2 and 6 mAh cm–2 were performed by Al2O3@MOF-C electrodes. Good performances were also obtained for Li–sulfur and LiFePO4 batteries. The performances of Al2O3@MOF-C@Li were compared with Li foil and Cu@Li in full cell configurations. The electrochemical tests of full cells based on Al2O3@MOF-C@Li indicated that this Al-based functional host matrix can enhance the Li-utilization and lead to significant enhancement of the cycling performance of Li anodes.